Impact of oral nutritional supplements (ONS) on growth outcomes and IGF-1 level in underweight older children and young adolescents (5-14 years) with short stature and no systemic disease: High versus normal calories density formula: Oral nutritional supplements (ONS) on growth outcomes in children and adolescents - De Sanctis, Vincenzo; Soliman, Ashraf; Elsiddig , Suhair; Alyafei, Fawziya; Alaaraj , Nada; Itani, Maya; Jour, Celine; Elawwa, Ahmed (Acta Biomedica Atenei Parmensis, 2021)
Abstract. Objectives: This controlled trial investigated the effects of energy-dense pediatric oral nutritional supplements ONS versus standard ONS in pediatric patients requiring oral nutritional support for low body mass index (BMI) or weight gain per day (WGD) below the average for age and sex.  Patients and Methods: 34 children and adolescents (mean age 10.2 years) with faltering growth requiring ONS were randomized to cONS (n =22) or sONS (n = 12) for a year. We recorded their weight (WT), height (HT) and calculated height growth velocity (GV), Ht-SDS, BMI, WGD, every 3 months for a year.  Results: The WGD, height growth velocity (GV: cm/year), and Ht-SDS increased significantly, in both groups, during the year of ONS. The use of the cONS resulted in significantly greater mean total WGD and BMI-SDS after 6 months and 1 year, compared to the sONS group. The increase in IGF1-SDS was significantly higher in the cONS groups versus the sONS group. Moreover, the WGD was correlated significantly with the height GV during the year of ONS intake. Conclusions: ONS improved the growth of underweight old children and adolescents who had no systemic illness. There was a significantly higher WGD and BMI-SDS in the group on cONS compared to those on sONS. In both groups, long-term use of ONS significantly improved Ht-SDS.